The determinants and extent of crop diversification among smallholder farmers: A case study of Southern Province, Zambia - Sichoongwe, Kiru; Mapemba, Lawrence; Ng'ong'ola, Davies; Tembo, Gelson (International Food Policy Research Institute, 2014)
This study analyzed the determinants of crop diversification as well as the factors influencing the extent of crop diversification by smallholder farmers in Southern province. The study used secondary data from the Central Statistical Office of Zambia. Results from a double-hurdle model analysis indicates that landholding size, fertilizer quantity, distance to market, and the type of tillage mechanism adopted have a strong influence on whether a farmer practices crop diversification. Our findings have important implications for policies that are designed to enhance crop diversification. In particular, our results suggest the need for government to consider undertaking policies that will enhance farmers’ access to and control over land, that will provide farmers with improved access to agricultural imple-ments like ploughs, and that will bring trading markets closer to farmers.